Primary Splenic Torsion in Lesser Grison (Galictis cuja) - Flores Moraes, Lilian; Machado Südecum, Joana; Depelegrin, Carolina; Morel, Ana Paula; Favreto, Isadora; De Araújo Roll, Alessandra; Müller da Silva, Taiara; Guarise, Raquel (Acta Scientiae Veterinariae, 2024)
Background: The lesser grison (Galictis cuja) is a mammalian species belonging to the mustelid family, commonly found in Brazilian zoos and rehabilitation centers. Despite the high prevalence of this species in Brazil, information on the diseases affecting these animals and their respective treatments is limited. This underscores the importance of case reports in this context. While splenic torsions are considered rare and are more commonly diagnosed and reported in dogs, they can also occur in other species, such as ferrets. Clinical signs are nonspecific, complicating the diagnosis, which is typically achieved through ultrasound with color Doppler assistance, revealing parenchymal, positional, and blood flow alterations, or therapeutic diagnosis through exploratory celiotomy. The aim of this study is to report a clinical and surgical case of primary splenic torsion in a lesser grison (G. cuja) from a zoo in southern Brazil. Case: A 8-year-old, uncastrated, 1.4 kg animal presented with a history of lethargy, anorexia, vomiting, and diarrhea. Clinical examination revealed dehydration and moderate abdominal pain, with palpation suggestive of splenomegaly and spleen displacement. The animal was hospitalized for treatment, and a complete blood count, biochemical tests, and abdominal ultrasound with color Doppler were performed. The blood test indicated anemia, while the abdominal ultrasound revealed an enlarged spleen in an atypical location, displaced cranially and to the right, with negative Doppler color signal throughout the organ. Surgical intervention was chosen, utilizing conventional splenectomy. Physical restraint was achieved with leather gloves and a snare. Anesthetic induction was performed with intravenous propofol, followed by periglottic anesthesia with lidocaine upon loss of eyelid and mandibular reflexes. Orotracheal intubation used a 2.5 tube. Transverse abdominal plane block with lidocaine at 6 mg/kg was administered at 2 points lateral to the incision site. General anesthesia was maintained with vaporized isoflurane in 100% oxygen at variable rates (0.4 to 0.8%). Exploratory celiotomy began with a pre-umbilical mid-ventral incision of 5 cm, accessing the abdominal cavity through the linea alba. After locating and exteriorizing the spleen, torsion of vessels in the splenic hilum region was observed. No complications occurred during the procedure, and the animal had a smooth anesthetic and surgical recovery. Discussion: Despite the preferred treatment for dogs with splenic torsion being splenectomy, there are disagreements among authors. Some advocate for detorsion of the spleen and assessment of associated injuries before opting for removal if the organ remains functional. The spleen returns to its normal size within minutes, but its normal position cannot be guaranteed, and there is no way to prevent future torsion. Moreover, detorsion may allow toxic material from necrosis to enter circulation, justifying the preference for spleen removal by some authors. In conclusion, diagnostic methods involving ultrasound, along with color Doppler, confirmed by exploratory celiotomy, and the chosen surgical technique, were satisfactory for treating the reported case. Keywords: Mustelidae, spleen, acute abdomen, ultrasonography. Título: Torção esplênica primária em furão-pequeno (Galictis cuja) Descritores: Mustelidae, baço, abdômen agudo, ultrassonografia.